Pembuatan Bioplastik Berbasis Pati Sagu Dengan Modifikator Asam Sitrat Dan Filler Carboxymethyl Cellulose (CMC) - Dewi Maya Sari; Syelvia Putri Utami; Bahruddin Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Bioplastic is one of the organic plastic that has been used as an eco-friendly food packagings whether has ability to degraded by nature. Sago starch has a potential to become raw material for bioplastics manufactured, and adding a carboxymethyl cellulose (CMC) aims to increase the tensile strength. The purposes of this research are determine the effect of sago starch, citric acid, CMC and glycerol of the characteristics bioplastics. Bioplastics product was characterized by few tests such as tensile strength (tensile strenght), elongation (elongation at break), and biodegradation. The analysis showed that filler CMC, plasticizer glycerol, and citric acid give an impact to mechanical properties of bioplastic. The best composition is bioplastic with (CMC 25% b/b, 25% b/b glycerol and 3% citric acid b/b) which is tensile strength of 8.23 MPa, elongation of 24,20%, and biodegradation 59,01%. Keyword: Bioplastic, filler, plasticizer, cross-linking agent, tensile strength